Willingness to communicate in English among Malaysian undergraduates at a public university - Abd Razak, Fatin Nabila (2021)
Willingness to Communicate (WTC) is notably the most significant construct to facilitate second language (L2) communication. However, studies related to WTC in Malaysia remain scarce and few available past studies failed to simultaneously include the three most significant variables predicting WTC (MacIntyre et al., 1998 & Yashima, 2002). Hence, this study aimed to investigate the interrelationships between the three affective variables affecting L2 WTC namely (1) communicative confidence, (2) motivation in learning L2, (3) international posture as conceptualised in the Heuristic Model of L2 WTC by MacIntyre et al. (1998) and Yashima (2002). The present study added three other constructs to help demonstrate the social circumstance in Malaysia among Malaysian undergraduates in a public university. The three constructs demonstrating the Malaysian social circumstance are (1) WTC in English based on four language use domains (education, family, friendship, and transaction), (2) Ethnic Group Affiliation (EGA), and (3) living area. Specifically, this quantitative study utilised Partial Least Square-Structural Equation Modelling (PLS-SEM) as the tool of data analysis. . The data was gathered from 540 public university undergraduates with a nine-construct questionnaire structured and adapted to address the study constructs. Following the data analysis, it was revealed that communicative confidence was the strongest predictor of WTC in English among all language use domains. The implicit motivation-WTC relationships through communicative confidence were also substantial in all language use domains. Notably, direct relationships between motivation in language-learning and WTC in all language use domains were significant. On another note, international posture was significant to WTC in English involving all language use domains excluding the family domain. Although EGA positively correlated to the education domain, a negative relationship was detected in the family domain. Additionally, the mediating effect of international posture between the EGA-WTC in English correlation was significant in all domains excluding the family domain. Regarding the living area, the outcome revealed that undergraduates living in urban areas possessed higher communicative confidence that encouraged more WTC in English than undergraduates in rural counterparts across all language use domains. In this light, this research affirmed the implementation and used of the Heuristic Model of L2 WTC by MacIntyre et al. (1998) in the local context. As such, the accountability of various language use domains, intra-group EGA factors, and undergraduates’ living areas was unquestionably essential as proven in the current research. Overall, the study has suggested the affective variable of communicative confidence as the variable that should be given utmost attention in English language learning alongside other affective variables. The study has also pointed out communicative confidence as the affective variable most lacking among the English language learners living in rural areas as compared to the English language learners living in the urban areas. Hence, future studies can be conducted to test the validation of these results in different contexts of language learning. Focus should also be given towards identifying ways to increase English language learners’ communicative confidence especially through reducing their language anxiety and increasing their self-perceived competency.